PENDAMPINGAN BACA TULIS AL-QUR’AN MENGGUNAKAN METODE IQRA’ MELALUI PROGRAM RUMAH QUR’AN DI KELURAHAN KALUMBUK, KECAMATAN KURANJI, KOTA PADANG - Zaky, Muhammad; Kustati, Martin; Amelia, Rezki; Gusmirawati (Tashdiq: Jurnal Kajian Agama dan Dakwah, 2024)
This mentoring aims to determine children's ability to read and write the Qur'an in Kalumbuk Village, Kuranji District, Padang City. Assistance is carried out by face-to-face learning to children, this assistance uses the iqra' method. The iqro' method is one of the methods in reading and writing the Qur'an that is effectively used for early childhood, the iqro' method is equipped with a practical tajweed book and relatively in a short time. This method emphasizes reading with fashih and correct according to the makhraj. The method used in conducting this research is by using the Participatory Active Research (PAR) method where researchers participate in every activity carried out during the research. The stages of this research begin with analyzing the needs of children in learning the Qur'an, then designing activities, implementing activities and evaluating the transformation results of the activities that have been carried out. The results of the study that with the assistance can improve the ability of the children of the qur'an house in reading and writing al qu'an. It can be seen the motivation of the children of the Qur'an house in reading the Qur'an properly and correctly. The results given are considered good, making the participants' ability to write and read increase and the knowledge they have about religion increases. Given the magnitude of the benefits provided in this service program.